2020
DOI: 10.3390/ijerph17082913
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care Is Associated with Medical Costs and Inpatient Days in Children with Cerebral Palsy

Abstract: Background: Children with cerebral palsy (CP) place a considerable burden on medical costs and add to an increased number of inpatient days in Taiwan. Continuity of care (COC) has not been investigated in this population thus far. Materials and Methods: We designed a retrospective population-based cohort study using Taiwan's National Health Insurance Research Database. Patients aged 0 to 18 years with CP catastrophic illness certificates were enrolled. We investigated the association of COC index (COCI) with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“… Worrall 2011 ; Canada [ 76 ] RC To examine the relationship between continuity of family physician care and all-cause mortality and acute hospitalizations Sample from Newfoundland and Labrador portion of the National Diabetes Surveillance System (NDSS) database linked to provincial FFS physician billing database 305 older people with DM (age ≥ 65 years) 1998-1999 UPC 7/9 Over 3 years No Death and hospitalization rate Higher COC group had significantly lower likelihood of hospitalizations than lower COC group (54.5% and 67.5%, respectively, p =0.027). Yang 2020; Taiwan [ 77 ] RC To investigate the association of COC index (COCI) with medical costs and inpatient days, and investigate the possible clinical characteristics affecting the outcome Taiwan’s National Health Insurance Research Database 3234 patients aged 0 to 18 years with cerebral palsy catastrophic illness 2000-2013 COCI 8/9 Single year No Medical costs and the number of inpatient days over 5 years Five-year inpatient days for a child in the low COC group were longer than for a child in the high COC group (8 days more, p < 0.001). Five-year medical costs for a child in the low COC group were higher than for a child in the high COCI group (US$1656 more, p = 0.016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Worrall 2011 ; Canada [ 76 ] RC To examine the relationship between continuity of family physician care and all-cause mortality and acute hospitalizations Sample from Newfoundland and Labrador portion of the National Diabetes Surveillance System (NDSS) database linked to provincial FFS physician billing database 305 older people with DM (age ≥ 65 years) 1998-1999 UPC 7/9 Over 3 years No Death and hospitalization rate Higher COC group had significantly lower likelihood of hospitalizations than lower COC group (54.5% and 67.5%, respectively, p =0.027). Yang 2020; Taiwan [ 77 ] RC To investigate the association of COC index (COCI) with medical costs and inpatient days, and investigate the possible clinical characteristics affecting the outcome Taiwan’s National Health Insurance Research Database 3234 patients aged 0 to 18 years with cerebral palsy catastrophic illness 2000-2013 COCI 8/9 Single year No Medical costs and the number of inpatient days over 5 years Five-year inpatient days for a child in the low COC group were longer than for a child in the high COC group (8 days more, p < 0.001). Five-year medical costs for a child in the low COC group were higher than for a child in the high COCI group (US$1656 more, p = 0.016).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies out of eight focusing on avoidable hospitalization or ACSC reported the ORs, which varied from 1.12 [ 65 ] (short-term diabetes-related) to 2.29 [ 64 ] (COPD-related) for lower COC (compared to higher COC). From the studies reporting associations with costs, three reported monetary values in US dollars, whereby higher COC was associated with $1656 [ 77 ]-$4045 [ 43 ] lower total medical costs.…”
Section: Resultsmentioning
confidence: 99%
“…20 Such high proportions are striking in this vulnerable population given that lapses in care have been shown to be associated with a three-fold increased risk of requiring an urgent surgical or catheter-based cardiac intervention. 21 Similarly, poorer health outcomes have been observed with discontinuous care among pediatric and AYA populations with other chronic health conditions (CHCs), such as cystic fibrosis, 22 cerebral palsy, 23 and diabetes. 24 Conversely, higher continuity of care has been associated with lower health care costs and health care use across various patient populations from multiple countries and settings, 25 emphasizing the importance of prioritizing effective and seamless health care transitions, particularly in the at-risk AYA population.…”
Section: Health Care Transition In the General Populationmentioning
confidence: 99%
“…To date, the literature has identified the features of transition practices, the perspectives of professionals and experiences of young adults and their families with the transition process, including barriers faced 18–21. Several reviews have explored transition among young adults with physical, mental health, endocrine, neurological and gastrointestinal conditions and quantified the effectiveness of transition practices 15 17 22–28. However, these findings may not apply to young adults with neurodevelopmental disorders, due to the complexity of the disorders and the increased risk of developing other serious health problems as they age.…”
Section: Introductionmentioning
confidence: 99%